2002
DOI: 10.1128/iai.70.3.1443-1452.2002
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with Pneumococcal Conjugate Vaccines with LT-K63, a Nontoxic Mutant of Heat-Labile Enterotoxin, as Adjuvant Rapidly Induces Protective Immunity against Lethal Pneumococcal Infections in Neonatal Mice

Abstract: Immunization with pneumococcal polysaccharides (PPS) conjugated to tetanus toxoid (TT)(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 67 publications
12
83
1
2
Order By: Relevance
“…This impaired IgG2a response in neonatal mice was also shown by significantly higher IgG1/IgG2a ratio compared to adult mice (10.4 vs. 2.2; p = 0.014). In agreement with our previous results [34], the reduced protective efficacy of the Pnc1-TT vaccine in neonates was related to the impaired early life IgG response to its PS moiety and lack of IgG2a response.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This impaired IgG2a response in neonatal mice was also shown by significantly higher IgG1/IgG2a ratio compared to adult mice (10.4 vs. 2.2; p = 0.014). In agreement with our previous results [34], the reduced protective efficacy of the Pnc1-TT vaccine in neonates was related to the impaired early life IgG response to its PS moiety and lack of IgG2a response.…”
Section: Resultssupporting
confidence: 93%
“…Our previous studies have shown that immunization of mice with conjugate vaccines can induce PS Abs and protective immunity in early infancy, but both immunogenicity and protective efficacy is significantly lower than in adults [34,42]. This murine infant immunization model against S. pneumoniae clearly reproduces the main features of human infant immune responses to native capsular PPS and pneumococcal conjugate vaccines, as shown for serotypes 1, 6B and 19F, as well as the relative protective efficacy of such vaccines.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations